2003
DOI: 10.1046/j.1365-2958.2003.03802.x
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant cardiolipin metabolism in the yeast taz1 mutant: a model for Barth syndrome

Abstract: SummaryIn eukaryotic cells, the acyl species of the phospholipid cardiolipin (CL) are more highly unsaturated than those of the other membrane phospholipids. Defective acylation of CL with unsaturated fatty acids and decreased total CL are associated with Barth syndrome, an X-linked cardio-and skeletal myopathy attributed to a defect in the gene G4.5 (also known as tafazzin). We constructed a yeast mutant ( taz1 ) containing a null mutation in the homologue of the human

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
184
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(207 citation statements)
references
References 35 publications
22
184
0
1
Order By: Relevance
“…Tafazzins mediate the late steps in the cardiolipin biosynthesis pathway, namely the acyl modifications that lead to its characteristic acyl pattern (Vreken et al, 2000;Vaz et al, 2003;Xu et al, 2003;Gu et al, 2004). Although human mitochondria predominantly contain cardiolipin with unsaturated C 18 fatty acids, cardiolipin of yeast contains equal amounts of oleoyl (18:1) and palmitoleoyl (C16:1; Jakovcic et al, 1971).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Tafazzins mediate the late steps in the cardiolipin biosynthesis pathway, namely the acyl modifications that lead to its characteristic acyl pattern (Vreken et al, 2000;Vaz et al, 2003;Xu et al, 2003;Gu et al, 2004). Although human mitochondria predominantly contain cardiolipin with unsaturated C 18 fatty acids, cardiolipin of yeast contains equal amounts of oleoyl (18:1) and palmitoleoyl (C16:1; Jakovcic et al, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported a growth defect for taz1⌬ cells on nonfermentable media at elevated temperature (Vaz et al, 2003;Gu et al, 2004). While analyzing the functionality of the Taz1 HA at different temperatures, we compared the growth of cells expressing Taz1 HA to wild type and the taz1⌬ mutant.…”
Section: Effect Of Taz1 Deletion On Inner Membrane Protein Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…Lipids were extracted from the lyophilized cell pellets using the previously reported method [33]; 25 μL of heptadecanoic acid ethyl ester was used as the internal standard. FAEEs in the total lipid extracts were purified by preparative TLC [9] using TLC Silica gel 60 F254plates (Merck, Darmstadt, Germany) and the solvent system of heptane, 2-propanol and acetic acid in the ratio 95:5:1 (v/v/v).…”
Section: Methodsmentioning
confidence: 99%